"And you shall tell your son" : identity and belonging as shaped by the Jewish holidays - Peleg, Itzik (Academic Studies Press, 2022)
"The cycle of Jewish holidays reflects a sense of identity with, and belonging to, the Jewish people, while simultaneously shaping that identity and sense of belonging. Throughout the generations, observance of the holidays has developed and changed, thus enabling generations of Jews, in their various communities, to define their own national identity and sense of belonging"--